Still travelling : my life as a Leyland brother and beyond - Leyland, Mal (Crows Nest: Allen & Unwin, 2015)
Next year is the 50th anniversary of the making of the Leyland Brothers' ground-breaking documentary, Down the Darling, which records Mike and Mal Leyland travelling down the Darling. Their film was sold to Channel 9 and later to the BBC. It was shown in 65 countries and selected by the Australian Government to be shown at Expo 67 in Canada. Unless you were alive and watching Australian TV in the mid-60s through to 1980, when they were at the peak of their popularity, it is hard to convey the impact of these two pioneer outback adventurers and film-makers. An obituary written when Mike Leyland died, in 2009, their numerous TV programs were described as a 'quirky travel show', watched by more than 2.5 million people at its peak. It featured the brothers in unusual or far-flung places around Australia, which viewers had asked them to visit